XXI April International Academic Conference on Economic and Social Development, April 6–10, 2020, Moscow - Board, Editorial (Journal of Economic Sociology, 2019)
On April 6–10, 2020 in Moscow, National Research University Higher School of Economics (HSE Univer-sity), with the support of the World Bank, will be hosting the XXI April International Academic Conference on Economic and Social Development. The Conference’s Programme Committee will be chaired by Professor Evgeny Yasin, HSE University’s academic supervisor.T he Conference features a diverse agenda concerning social and economic development in Russia. The Conference programme will include presentations by Russian and international academics, roundtables and plenary sessions with participation of members of the Government of the Russian Federation, government officials, business representatives, and leading Russian and foreign experts.